Small World: If Germany Only Trades With Democracies - Lukas Menkhoff (Wirtschaftsdienst)
Abstract The last few years have shown the downside of the German export model, i. e. Germany’s dependency on its trading partners. This is particularly painful at present with regards to Russia and potentially China. Thus it seems reasonable to focus German trade on democratic countries. However, whatever benchmark one takes, the democratic world remains small and does not increase in importance. Moreover, the less democratic countries are tentatively poorer which implies that their trade structure follows a specific pattern; in particular these countries have a higher share of commodity exports which are hardly available in Germany or Europe. Consequently, the economic costs of such a self-imposed restriction would be high.